(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
BACKGROUND Hand washing has been considered a measure of personal hygiene for centuries and it is known that an improper hand hygiene by healthcare workers is responsible for about 40% of nosocomial infections. Therefore, surgical hand preparation is a critical element for healthcare safety in order to reduce microbial contamination of surgical wound in case of non detected break of the gloves. The aim of our study is to evaluate the efficacy three antiseptics: Povi-iodine scrub; EPG (Ethanol, Hydrogen Peroxide, Glycerol, recommended by WHO), and common marseille soap type in a liquid formulation. METHODS It was designed a randomized, double-blind, single-center study conducted in the University Hospital of Messina, from January to June 2013. We asked operators to put the fingertips of their right hand (if not left-handed) for one minute on the PCA medium, before washing with the three types of antiseptics, and after washing and drying. Drying was made using sterile gauzes or disposable wipes. Then, we measured the number of colony forming units per mL (CFU/mL) and calculated the percentage of microbial load reduction. RESULTS 211 samples have been considered for statistical analysis: in 42 samples, in fact, initial microbial load was lower than after washing. Washing with EPG reduced CFU/ml from a mean of 38,9 to 4,1 (86,5% reduction), washing with povi-iodine scrub from 59,55 to 12,9 (75,9% reduction) and washing with Marseille soap from 47,26 to 12,7 (64,3% reduction). CONCLUSIONS Our study shows that washing with EPG has superior efficacy in CFU reduction. Antiseptic hand washing, however, cannot be considered the only measure to reduce infections: the anomaly of some results (initial microbial load lower than after washing) demonstrates that drying is an essential phase in the presurgical preparation. Therefore, hand hygiene must be part of a more complex strategy of surveillance and control of nosocomial infections